Quality of the Polish traditional mountain sheep cheese 'oscypek' - Drozdz A. (Production systems and product quality in sheep and goats, 2001)
The traditional technology of oscypek production was analysed in three shepherd's huts. Particular cheese production phases were examined, the acidity of milk and whey was defined for particular production phases as well as curd yield and chemical composition of the cheese. 6.0 litres of milk are needed to produce 1 cheese of 800 g. Oscypek from various shepherd's huts do not differ in form or mass, but in the amount of water and acidity. The most stable elements of the cheese are salt and protein. Average oscypek contains 30-35 per cent of water, 30 per cent of fat, 29 per cent of protein, 2-3 per cent of salt and about 10 per cent of mineral substances. Both milk and the cheeses do not always meet the official micro-biological standards. In the future the producers will have to mark their products with permanent marks that will allow for their identification.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)